2020
DOI: 10.1038/s41433-020-01159-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraocular lens formulas using total keratometry in eyes with previous myopic laser refractive surgery

Abstract: Objectives This comparative study aimed to determine if total keratometry (TK) from IOLMaster 700 could be applied to conventional formulas to perform IOL power calculation in eyes with previous myopic laser refractive surgery, and to evaluate their accuracy with known post-laser refractive surgery formulas. Methods Sixty-four eyes of 49 patients with previous myopic laser refractive surgery were evaluated 1 month after cataract surgery. A comparison of the prediction error was made between no clinical history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
3
28
1
Order By: Relevance
“…UCVA, BCVA, and prediction error were not significantly different between FLACS and conventional PCS. The Barrett True-K formula is one of the most accurate IOL calculation formulas for patients with a previous history of CRS 15 , and the prediction error of the Barrett True-K formula was − 0.24, which was similar to those of our study.…”
Section: Discussionsupporting
confidence: 89%
“…UCVA, BCVA, and prediction error were not significantly different between FLACS and conventional PCS. The Barrett True-K formula is one of the most accurate IOL calculation formulas for patients with a previous history of CRS 15 , and the prediction error of the Barrett True-K formula was − 0.24, which was similar to those of our study.…”
Section: Discussionsupporting
confidence: 89%
“…UCVA, BCVA, and prediction error were not signi cantly different between FLACS and conventional PCS. The Barrett True-K formula is one of the most accurate IOL calculation formulas for patients with a previous history of CRS, 17 and the prediction error of Barrett True-K formula was − 0.24, which was similar to those of our study (-0.30 in FLACS and − 0.25 in conventional PCS).…”
Section: Discussionsupporting
confidence: 88%
“…Their best combination gave RPE within ±0.50 D and ±1.00 D for 67% and 93%, respectively. 44 Two recent studies compared no-history formulas with conventional formulas using TCP from an IOLMaster 700: Yeo et al found the best prediction errors using TCP with the EVO (a new unpublished formula), Barret TK NH, and Haigis formulas with 69%, 64% and 64%, respectively, within ±0.5 D and 83% within ±0.75 D for all three formulas, which was better than both the Barret TK NH and the Haigis-L. 45 Lawless et al found the best results with the Barret TK (TCP), followed by Barret TK NH and Haigis TCP with; 35%, 38% and 40%, respectively, within ±0.25 D; 75%, 63% and 60%, respectively, within ±0.50 D; 90%, 83% and 80%, respectively, within ±0.75 D. 46 Both these studies show that the use of TCP is likely to improve IOL-calculations in post-LVC patients. This could be expected as and both the Haigis-L and Barret TK NH uses a regression equation, with its inherent variance, to account for the altered corneal power in post LVC corneas.…”
Section: Discussionmentioning
confidence: 99%